Assessing The Influence Of Ownership Structure And Board Diversity On Capital Structure Adjustment Speed: Evidence From Malaysia - Ibrahim, Hanis Adiela (2022)
This study estimates the adjustment speed towards target capital structure based on 237 non-financial firms listed on Bursa Malaysia for the period of 2012-2017. This study validates the existence of target capital structure in Malaysian firms found in previous studies and revealed that the speed of adjustment for the sample firms ranges between 33.6% to 45% annually, depending on the leverage proxies used.